The impact of COVID-19 pandemic in teaching and learning on health academic courses (Research, Society and Development, 2022)
The COVID-19 pandemic caused major changes in the current panoramas of society. In this sense, the teaching and learning process during the pandemic period was also affected, largely due to the social isolation that opened up margins for remote teaching that divides opinions about its effectiveness. The objective of the present work was to evaluate the impact of the COVID-19 pandemic on the teaching and learning processes of academic courses in the health area. To this end, we carried out a systematic literature review study through journals available in the PubMed database. At first, 112 articles were identified in the search and, after applying the inclusion and exclusion criteria, 15 articles were selected, which were read and added to our work. The results showed that the COVID-19 pandemic had significant impacts on the teaching-learning process, requiring students and teachers to reinvent themselves in their way of learning and teaching. Implementing remote learning has advantages and disadvantages that divide students around the world. Educational institutions should invest in the coming years in infrastructure that contemplates the new trends in teaching and learning, offering training courses for teachers and employees with a view to developing the necessary skills for the new practices that will be the future of education. The gap in the teaching of courses in the health area can be filled with short courses and workshops offered by the health education institution with the aim of complementing the training of these future professionals.